2001
DOI: 10.1016/s0168-1923(00)00225-2
|View full text |Cite
|
Sign up to set email alerts
|

Gap filling strategies for defensible annual sums of net ecosystem exchange

Abstract: Heightened awareness of global change issues within both science and political communities has increased interest in using the global network of eddy covariance flux towers to more fully understand the impacts of natural and anthropogenic phenomena on the global carbon balance. Comparisons of net ecosystem exchange (F NEE ) responses are being made among biome types, phenology patterns, and stress conditions. The comparisons are usually performed on annual sums of F NEE ; however, the average data coverage dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
1,287
7
23

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,704 publications
(1,374 citation statements)
references
References 42 publications
27
1,287
7
23
Order By: Relevance
“…Gaps in O 3 concentrations caused by instrument malfunction and power shortage were filled using two methods. If missed data spanned less than 4 sequential gaps, the linear interpolation method was used, otherwise, the mean diurnal variation method was applied (Falge et al, 2001). (Fig.…”
Section: Calculation Of O 3 Concentration-based Indicesmentioning
confidence: 99%
“…Gaps in O 3 concentrations caused by instrument malfunction and power shortage were filled using two methods. If missed data spanned less than 4 sequential gaps, the linear interpolation method was used, otherwise, the mean diurnal variation method was applied (Falge et al, 2001). (Fig.…”
Section: Calculation Of O 3 Concentration-based Indicesmentioning
confidence: 99%
“…The CH 4 fluxes were gap filled based on the exponential soil temperature relationship presented by Jackowicz-Korczyński et al (2010) while with the CO 2 flux signal two different approaches were applied. The daytime CO 2 fluxes recorded during the growing season were gap filled by applying the light response equation (1) while the rest of the fluxes were parameterized with the night respiration equation (2) (Falge et al 2001).…”
Section: Gap Fillingmentioning
confidence: 99%
“…For both sites, the smaller classes of 8, 4 and 2 K have a similar performance, indicating that it is unnecessary to bin the data into temperature classes smaller than 8 K. This range is larger than the 4 K temperature class used by Falge et al (2001) for a variety of sites including croplands and the 2 K temperature class used by Ruppert et al (2006) for a forest site. They also reported that additional time windows do not significantly improve the temperature binning method, because the existing long-time seasonal temperature response of the long-living and slow-growing coniferous forest is already covered by the time-independent allocation of the values into the temperature bins.…”
Section: Temperature-binning Schemementioning
confidence: 92%
“…However, data gaps in the eddy-covariance technique are unavoidable and limit the carbon budget estimate. An average of 35% air or soil temperature, vapor pressure deficit (VPD), and soil water availability (Greco and Baldocchi, 1996;Falge et al, 2001). Amongst all of these, mean diurnal variation, look-up table, and non-linear regression are the most commonly used methods.…”
Section: Introductionmentioning
confidence: 99%